Carbonyl–Olefin Cross‐Metathesis Through a Visible‐Light‐Induced 1, 3‐Diol Formation and Fragmentation Sequence. Issue 49 (8th November 2018) - Pitzer, Lena; Sandfort, Frederik; Strieth‐Kalthoff, Felix; Glorius, Frank
Abstract: A visible‐light‐mediated approach to carbonyl–olefin cross‐metathesis is described. Photoinduced hole catalysis was used to promote the formation of 1, 3‐diols from aldehydes and styrenes, which were then readily fragmented under acidic conditions to form the cross‐metathesis products. The use of 1, 3‐diols as intermediates, rather than the energetically more demanding oxetanes, provides a new, orthogonal mechanistic strategy for carbonyl–olefin cross‐metathesis. Furthermore, this approach does not require any metals, ligands, or additives, and provides the products with high levels of E  selectivity. A mechanistic rationale is provided and supported by both theoretical calculations and experiments. Additionally, a practical synthesis of a new acridinium‐based photocatalyst, including full characterization, is presented. Abstract : XOXO : A carbonyl–olefin cross‐metathesis (COCM) is described. The method proceeds through a visible‐light‐induced hole‐catalyzed 1, 3‐diol formation and a subsequent acid‐induced Grob‐type 1, 3‐diol fragmentation. This strategy is orthogonal to existing COCM methods since, in contrast to difficult‐to‐access oxetanes, the key intermediates, 1, 3‐diols, are readily formed.